(untitled) (El-Wahat Journal for Research and Studies, 2025)
This study delves into the past to understand its contexts and explain current phenomena by tracing their historical roots. Through data collection, analysis, and scientific verification, the research aims to establish evidence for historical events and present results rigorously. It proposes a model for historical research methodology, highlighting the importance of past interactions and their influence on historical events. The study acknowledges the historical method’s role in uncovering both true and false events, emphasizing the importance of utilizing them for the present and future. It stresses the need to consider historical data, including Islamic theological aspects, to study the phenomenon and clarify relationships. The research acknowledges the possibility of source forgery or loss and the difficulty of generalizing results due to the unique nature of historical events. Finally, it emphasizes the link between the studied phenomena and specific circumstances, such as environment or religion. Keywords: History, Methodology, Creed, Divine Decree, Historical Research.